Pelatihan Bahasa Inggris di Panti Asuhan Nurul Jannah - Alfilail, Nur; Sudewi, Ni Ketut Putri Nila; Dewi, Puspita; Alawiyah, Rosidah; Ramdhani, Suciaty (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2023)
English skill is an essential skill to be mastered by students nowadays. Since its importance, students need to focus on developing this skill as early as they can. Nevertheless, not all institutions could provide sufficient material and skill to be taught in the class. Based on some observations, students in panti asuhan Nurul Jannah still have some mistakes in speaking using the English language. Thus, efficient English training was needed by students in panti asuhan Nurul Jannah. Lecturers from Bumigora university who were experts in English did community service in panti asuhan Nurul Jannah. This aimed to increase students' ability in English and improve some mistakes and language errors that were still done by the students. This community service was done by applying several methods such as speech, discussion, etc. After several meetings of the training, students in this orphanage showed positive attitude toward the training and most of the students could improve their ability in English.